Consensus guidelines for the management of pediatric medulloblastoma in low and middle-income countries - Naureen Mushtaq; Syed Ather Enam; Mohammad Hamza Bajwa; Fatima Mustansir; Erum Baig; Fatima Gauhar; Afia Arif; Ahsan Ali Khan; Syed Ahmer Hamid; Gohar Javed; et al. (Journal of the Pakistan Medical Association, 2024)
The management of medulloblastoma, a pediatric brain tumor, has evolved significantly with the advent of genomic subgrouping, yet morbidity and mortality remain high in LMICs like Pakistan due to inadequate multidisciplinary care infrastructure. This paper aims to establish evidence-based guidelines tailored to the constraints of such countries. An expert panel comprising neuro-oncologists, neurosurgeons, radiologists, radiation oncologists, neuropathologists, and pediatricians collaborated to develop these guidelines, considering the specific challenges of pediatric brain tumor care in Pakistan. The recommendations cover various aspects of medulloblastoma treatment, including pre-surgical workup, neurosurgery, neuropathology, chemotherapy, radiation therapy, and supportive care. They offer both minimum required and additional optional protocols for more advanced centers, ensuring comprehensive patient management with attention to complications and complexities encountered in Pakistan. The paper’s consensus guidelines strive for uniformity in healthcare delivery and address significant gaps in diagnosis, treatment, and follow-up of pediatric medulloblastoma patients. Keywords: Medulloblastoma, neuropathology, neurosurgery, radiation oncologists, brain neoplasms, paediatricians, morbidity, genomics